In-Depth Observation on the Microbial and Fungal Community Structure of Four Contrasting Tomato Cultivation Systems in Soil Based and Soilless Culture Systems - Grunert, Oliver; Hernandez-Sanabria, Emma; Buysens, Saskia; De Neve, Stefaan; Van Labeke, Marie-Christine; Reheul, Dirk; Boon, Nico (Frontiers in Plant Science, 2020)
As soil and soilless culture systems are highly dynamic environments, the structure of rhizosphere microbial communities is consistently adapting. Microbial-driven nitrogen conversion process are yet to be reported in soilless culture systems, and thus we aimed at surveying their impact on diversity and composition of bacterial communities across a 10-month period. We compared community metrics between organic soil fertilized with plant and animal-derived material and organic growing medium with fish effluent or supplemented with organic fertilizer. Bacterial community composition was monitored over time using phospholipid fatty acid analysis and 16S rRNA amplicon sequencing. Nitrogen dynamics and plant performance were assessed to provide insight on how bacterial diversity of soil and soilless microbial communities ultimately impacts productivity. Soil and soilless cultivating systems supplemented with different nitrogen-rich fertilizers differed on its characteristics throughout the experimental period. Multivariate analysis showed that plant length, pH, Flavisolibacter, phosphorus, chloride, ammonium, potassium, calcium, magnesium, sodium, electrical conductivity, nitrate, sulphate, and the bacterial genera Desulfotomaculum, Solirubrobacter, Dehalococcoides, Bythopirellula, Steroidobacter, Litorilinea, Nonomuraea were the most significant factors discriminating between natural soils supplemented with animal and plant by-products. The use of these by-products in the soil was positively associated with arbuscular mycorrhizal fungi (AMF), which may influence rhizosphere communities through root exudates and C translocation. Community structure was distinct and consistently different over time, despite the fertilizer supplementation. The fungal microbial community composition was less affected by pH, while the composition of the bacterial communities (Actinomycetes, Gram-negative bacteria and Gram-positive bacteria) was closely defined by soil pH, demonstrating the significance of pH as driver of bacterial community composition. Observed differences could be attributed to the highly dynamic nitrogen conversions on the four tomato cultivating systems, as net nitrogen mineralization contributed up to 80% to the plant-available nitrogen. Fertilizer application may be responsible for variations over time in the ecosystem. Knowledge about the microbial interactions in tomato cultivating systems opens a window of opportunity for designing targeted fertilizers supporting sustainable crop production.